Comparison of total serum immunoglobulin E and absolute eosinophil count levels among asthmatic and non-asthmatic children - Chaudhary, G S; Kumar, Avinash; Shashtri, Madhurmay; Chaudhary, Vidya (Indian Journal of Child Health, 2017)
Background: Immunoglobulin E (IgE) and associated cellular responses such as absolute eosinophil count (AEC) are responsible for allergic airway diseases. A hypersensitivity reaction initiated by immunological mechanisms, mediated by IgE antibodies, and eosinophils occur in allergic asthma. Objective: To compare the total serum IgE level and AEC levels among asthmatic and non-asthmatic children. Methods: The present study was conducted in the department of pediatrics and TB and Chest of a Medical College of North India from October 2015 to November 2016. Children from 3 years to 18 years, 30 with bronchial asthma and 30 healthy children were included in this study randomly. Results: The mean total serum IgE level in children with bronchial asthma was significantly higher (700.97±571.01 IU/ml) than that in healthy children (189.33±14.29 IU/ml). The mean AEC was also significantly higher in cases (746.63±492.02 cells/mm3) as compared to healthy children (220.23±121.69 cells/mm3). In bronchial asthma group, mean AEC increased with the increasing severity of asthma. Conclusion: The elevated level of total serum IgE and AEC may demonstrate the allergic etiology of asthma and hence, estimation of serum IgE and AEC levels can be considered as laboratory investigations in diagnosing cases of bronchial asthma.